EFFECTIVE WAYS TO IMPROVE LISTENING SKILLS AMONG INTERMEDIATE-LEVEL STUDENTS (Modern education and development, 2024)
This article explores effective strategies to improve listening skills among intermediate-level learners of English as a Foreign Language (EFL). It highlights the importance of listening as a fundamental skill for communication and examines the challenges faced by learners, such as anxiety, vocabulary limitations, and difficulty with natural speech pace. Drawing on research and literature, the article presents cognitive, metacognitive, and socio-affective strategies to enhance listening comprehension. It also discusses the role of multimedia tools and practical classroom activities, emphasizing the need for systematic training and consistent exposure to listening materials. This comprehensive guide aims to equip educators and learners with actionable insights for mastering listening skills.